Modeling a sprinboard in gymnastics - Lehmann, T.; Schleichardt, A.; Naundorf, F.; Knoll, Kl. (ISBS Proceedings Archive (Michigan), 2017)
For development and optimization of elements in gymnastics` vault, the knowledge of the angular momentum, take-off velocity and thus the forces on the springboard are of interest. A multi-body model was developed for the determination of forces. The following article describes the creation of a springboard model and therefore the identification and evaluation of physical parameters acting during movements.